E-Learning: Pros and Cons - Solovyova, O. V.; Соловйова, Ольга Володимирівна (Rome : Potere della ragione Editore, 2021)
The article deals with the problem of E-learning implementation into educational programs using information and educational resources. The positive and negative aspects of e-learning during mastering basic and additional professional educational programs is studied in this article.
Keywords: e-learning; educational process; gamification; interaction; personalization